Micropore Structural Characteristics and Influence Factors of Triassic Shale Gas Adsorption in the Ordos Basin - Yang, Fu; Ma, Dongmin; Duan, Zhonghui; Ren, Dazhong; Tian, Tao; Fu, Deliang (Frontiers in Physics, 2022)
Continental shale is investigated for potential shale gas reservoirs in the Tongchuan area, southern Ordos Basin. The kerogen macerals of Upper Triassic Chang 7 Shale are vitrinite 28–43%, exinite 4–7%, and inertinite 52–69%, and Ro is 0.85–0.88%, and the kerogen type is II. The total organic carbon (TOC) content is 9.75–29.92%, free hydrocarbon (S1) is 3.21–12.14%, pyrolysis hydrocarbon (S2) is 41.86–165.39%, and maximum pyrolysis temperature (Tmax) is 439–445°C. The mineral composition is mainly dominated by quartz 3.94–43.27%, followed by feldspar 9.65–30.07% and clay minerals 13.46–59%. Illonite/smectite (I/S) is the main clay mineral, accounting for 47–69%. The liquid nitrogen adsorption curve showed that the pore types were tubular and plate-like. The pores are mainly microporous (<2 nm) and mesoporous (2–50 nm) in size. Isothermal adsorption results show that Langmuir volume (VL) is 2.06–5.57 cm3 g−1, Langmuir pressure (PL) is 2.16–3.28 MPa, and shale adsorption capacity is small and easy to desorb. A quartz content less than 25% is negatively correlated with the specific surface area (SSA); otherwise, it is positively correlated. A clay mineral content less than 45% is negatively correlated with SSA; otherwise, it is positively correlated. The relationship between the carbonate content and pore structure is not obvious. Pyrite content less than 2% is positively correlated with SSA; otherwise, it is negatively correlated. The SSA is positively correlated with TOC, inertinite, and exinite and negatively correlated with vitrinite. The adsorbed gas content is positively correlated with the TOC content, SSA, inertinite content, and exinite content and negatively correlated with vitrinite.